Studi Eksperimental Pengaruh Variasi Serat Ilalang terhadap Kuat Tekan Beton Mutu K-150 - Iik Nurul Fadillah; Fakhri Fauzi Suwandi (Jurnal Talenta Sipil, 2026)
Concrete is a widely used construction material due to its high compressive strength and ease of construction. However, concrete is brittle and has low tensile strength, making it prone to cracking. One approach that can be investigated to modify concrete characteristics is the addition of natural fibers to the concrete mixture. This study aims to analyze the effect of adding thatch fibers on the compressive strength of K-150 grade concrete. The study was conducted experimentally using cube-shaped test specimens measuring 15x15x15 cm. The variations in the addition of thatch fibers used were 0%, 2.5%, 5%, and 10% of the cement weight. Compressive strength testing was carried out at 7 days, 14 days, and 28 days. The results showed that normal concrete without thatch fibers produced the highest compressive strength of 16.44 MPa at 28 days. The addition of 2.5% thatch fibers still produced a compressive strength that was relatively close to normal concrete, namely 16.31 MPa. However, the addition of 5% and 10% fiber resulted in a significant decrease in compressive strength to 7.11 MPa and 2.22 MPa, respectively. The decrease in concrete compressive strength was presumably influenced by increased porosity, decreased workability, and less homogeneous fiber distribution in the concrete mixture. Based on the compressive strength results, the addition of thatch fiber in small amounts, particularly 2.5% of cement weight, can still be considered as a concrete additive. However, its use needs to be limited because higher fiber contents significantly reduce the compressive strength of concrete.